Wearability issues of clothing products from the perspective of users (ModaPalavra e-periódico, 2022)
With the growth of the fashion market, production cycles become shorter and problems related to the wearability of clothing products become more common. For better assistance, it is understood to be essential to centralize these in the Clothing Product Development Process. In this sense, a way to bring them closer and understand their demands is through the identification of their problems. In order to identify the main problems encountered by users, related to the wearability of clothing products, this research, of a basic nature, qualitative approach and exploratory objective, uses classifieds with twenty respondents between 20 and 50 years old. Through this, problems related mainly to the regions of the ankles, wrists, chest and abdomen (female interviewees) were listed, as well as the abdomen, shoulders and calves (male interviewees). sense of better adapting the product - clothing to the characteristics of the users, minimizing the problems of wearability.
Keywords: Dressability; User; Clothing; User-centric design